PENGARUH INTEGRASI READING ALOUND-TWO STAY TWO STRAY TERHADAP MINAT DAN HASIL BELAJAR IPA BIOLOGI MATERI PERKEMBANGBIAKAN TUMBUHAN PADA SISWA KELAS IX SMP NEGERI 12 PAREPARE - Kurniati . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2019)
This study aims to determine (i) Interest in students learning in science (ii) Student learning outcomes in science. (iii) the influence of Reading Alound Two two stays on the interest of learners in science. (iv) the influence of Reading Alound two stay two stray strategy toward the students' learning interest in science. This study is an experimental research (quasy experiment) which takes into account several variables of interest and learning outcomes of students of class IX SMP Negeri 12 Parepare with the application of the model of Reading Alound Two stay two stray.. Expected research results (i) The interest in learning of students in Biology Science subjects in class IX in Parepare State Middle School which was taught by Reading Aloud-Two stay two stray learning models experienced an increase in the average value before and after treatment, which is in the high category . (ii) Learning outcomes of students in Biology Science class IX in Parepare State Middle School which were taught by Reading Aloud-Two stay two stray learning model experienced an increase in the average value before and after treatment which was in the high category. (iii) application Reading Aloud-Two stay two stray significantly influences students' biology learning interest in science. (iv) Application of Learning Reading Aloud-Two stay two stray significantly influences students' Biology science learning outcomes. Key words: Reading Almost Two Stay Two Stray, Interest and Learning Outcomes.